PENGARUH WORD OF MOUTH, KUALITAS PELAYANAN DAN PERSEPSI HARGA TERHADAP KEPUASAN KONSUMEN PADA MIE GACOAN GRESIK - Firnanda Amelia Yuniar (Cahaya Ilmu Bangsa, 2025)
This study aims to determine the effect of Word of Mouth, Service Quality, and Price Perception on Consumer Satisfaction at Mie Gacoan Gresik. This research uses a quantitative method, with data collection techniques involving the distribution of offline questionnaires, and the analysis used is multiple linear regression, with a sample consisting of 96 respondents. The research results indicate that all indicators are valid and reliable. The results of the T-test indicate that Word of Mouth, Service Quality, and Price Perception have a significant impact on Customer Satisfaction. The results of the F test state that Word of Mouth, Service Quality, and Price Perception have a significant effect on Customer Satisfaction.